Strategi Fundraising dalam Meningkatkan Dana ZIS pada LAZISNU Jawa Timur - Lian Fuad (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2024)
This study examines the fundraising strategies implemented by LAZISNU East Java to increase the collection of Zakat, Infak, and Sedekah (ZIS) funds. Using a qualitative approach, this research identifies both online and offline fundraising methods. Online strategies include utilizing websites, social media, and crowdfunding platforms to expand donor reach. Meanwhile, offline strategies involve fundraising through donation boxes, religious events, and collaborations with various organizations. The findings indicate that combining digital and conventional strategies can enhance donor participation, strengthen transparency, and build public trust in ZIS fund management. Factors such as institutional legality, well-structured programs, and social media utilization also contribute to the effectiveness of fundraising efforts. Thus, adaptive and innovative fundraising strategies play a crucial role in optimizing ZIS fund collection and ensuring the sustainability of philanthropic-based social programs